Carboxylated Photoswitchable Diarylethenes for Biolabeling and Super‐Resolution RESOLFT Microscopy - Roubinet, Benoît (Angew Chem Int Ed Engl, 2016)
Reversibly photoswitchable 1,2‐bis(2‐ethyl‐6‐phenyl‐1‐benzothiophene‐1,1‐dioxide‐3‐yl)perfluorocyclopentenes (EBT) having fluorescent “closed” forms were decorated with four or eight carboxylic groups and attached to antibodies. Low aggregation, efficient photoswitching in aqueous buffers, specific staining of cellular structures, and good photophysical properties were demonstrated. Alternating light pulses of UV and blue light induce numerous reversible photochemical transformations between two stables states with distinct structures. Using relatively low light intensities, EBTs were applied in biology‐related super‐resolution microscopy based on the reversible saturable (switchable) optical linear fluorescence transitions (RESOLFT) and demonstrated optical resolution of 75 nm.